Performance Indicators of Indian Railways at Glance - Murugaiah, V; Kumar, Raghavendra Prasanna (Ushus Journal of Business Management, 2017)
Indian Railways is aware of the need to be up-to-datewith modern technological developments and best globalpractices to cash on the growing opportunity in freight and passenger business and provide the desired level of service to its passengers and customers. In this research paper, an attempt is made to evaluate the overall performance of Indian railways over the last ten years &to study the comparative position of train accidents and measures to improve safety by Indian Railways. The outcome of the study will explain in detail about the efficiency of Indian railways. Indian railways has always shown keen interest in taking advantage of technology to provide safety for the passengers.